STRUCTURAL ENGINEERING ANALYSIS AND SEISMIC RETROFITTING OF HISTORICAL MOSQUE MINARETS IN THE INDONESIAN ARCHIPELAGO - Risang Setyobudi; Samira Mohammed; Anna Bakker (Yayasan Adra Karima Hubbi, 2025)
Historical mosque minarets in the Indonesian archipelago, vital components of cultural heritage, are situated in a high-seismicity region. Their unreinforced masonry (URM) construction presents a significant, yet unquantified, vulnerability, posing threats to public safety and heritage preservation. This study provides a quantitative structural engineering analysis to assess this seismic vulnerability and establish a methodological framework for evaluating seismic retrofitting interventions. A diagnosis-led approach was employed, integrating in-situ non-destructive diagnostics (NDT), ambient vibration testing (AVT) for dynamic characterization, and advanced non-linear finite element modeling (FEM) on representative case-study structures. Results reveal a critical gap between structural capacity and seismic demand. The models predict catastrophic failure at low peak ground accelerations (0.15g), far below the 500-year hazard level (>0.40g). Unique Indonesian materials (volcanic stone, weak mortar) render existing international fragility models inadequate for this typology. Indonesian minarets possess critical seismic deficiencies requiring urgent, scientifically-grounded intervention. The validated models serve as essential tools for designing and testing culturally appropriate, minimally invasive retrofitting strategies to ensure the preservation of this irreplaceable built heritage.